Antecedents and outcomes of employee voice and silence behaviours in Nigerian tertiary educational institutions - Umar, Malami (unimas, 2016)
Employee voice and silence behaviours, commonly exhibited by employees in organisations, have not been the subject of empirical study over the years. Existing studies have not explored these phenomena jointly, and the majority of related investigations have been conducted in countries with Western cultures. This study jointly examines the phenomena of employee voice and silence behaviours through the lens of social exchange theory to fill the gap in the research and literature. The study explored the antecedents and outcomes of employee voice and silence behaviours by remodelling the employee silence model. The model was expanded by induction of outcomes and moderating variables. The quantitative method was adopted. The positivist research paradigm was utilised by the study based on the philosophical assumption of objective and single reality and the epistemological belief that the research should remain distanced from the reality. A questionnaire was used to collect data from 500 employees of tertiary educational institutions in the North-west geopolitical zone of Nigeria, of which 363 usable responses were received.